2020
DOI: 10.1620/tjem.250.173
|View full text |Cite
|
Sign up to set email alerts
|

Saline Solution Irrigation of the Bile Duct after Stone Removal Reduces the Recurrence of Common Bile Duct Stones

Abstract: Common bile duct (CBD) stone is a relatively common but potentially life-threatening disease. Endoscopic sphincterotomy (EST) has been performed as standard therapy for CBD stones, but the rate of recurrence of CBD stones is high. Risk factors have been poorly defined, and no effective means for the prevention of the recurrence of CBD stones have been established so far. We aimed to identify significant risk factors for the recurrence of bile duct stones. This study included 477 patients (231 women; mean age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
5
1
Order By: Relevance
“…Some studies have reported that saline irrigation can reduce the residual stone rate after endoscopic stone removal, especially if the lithotripsy technique is required. 7 , 9 , 10 , 12 Our previous study confirmed that 94% of patients were free of stone fragments and biliary sludge after intermittent irrigation with 100 ml saline. 11 However, there are few reports about residual stone fragments and the recurrence of CBDS.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Some studies have reported that saline irrigation can reduce the residual stone rate after endoscopic stone removal, especially if the lithotripsy technique is required. 7 , 9 , 10 , 12 Our previous study confirmed that 94% of patients were free of stone fragments and biliary sludge after intermittent irrigation with 100 ml saline. 11 However, there are few reports about residual stone fragments and the recurrence of CBDS.…”
Section: Introductionsupporting
confidence: 53%
“… 6 However, mechanical lithotripsy is one of the important risk factors for CBD stone recurrence. 7 Small stone fragments or bile sludge left after lithotripsy may become the primary nidus of stone recurrence. 8 A retrospective study found that the residual stone rate after endoscopic extraction was 25.9% (14/54).…”
Section: Introductionmentioning
confidence: 99%
“…Since recurrent stones are recurrent stones or residual stones, the location, size, and nature of the stones are different, and the structure of the bile duct and adjacent tissues and organs is also different from that of the first surgery. Therefore, the treatment is significantly more difficult and the surgical risk is greater compared with the first surgery [ 2 , 3 ]. Currently, the main secondary surgical procedures commonly used for these patients are endoscopic retrograde cholangiopancreatography (ERCP) [ 4 ], open common bile duct exploration (OCBDE) [ 5 ], and laparoscopic common bile duct exploration (LCBDE) [ 6 ], but there is no unified conclusion on which procedure is more effective.…”
Section: Prefacementioning
confidence: 99%
“…Alternatively, prophylactic saline irrigation of the biliary tract after ERCP may also reduce the recurrence of common bile duct stones. (24,30) Cholecystectomy Cholecystectomy after ERCP is still a controversial topic. The2017 UK guidelines for the treatment of choledocholithiasis stated that: All the cholecystolithiasis or patients with gallstones should undergo cholecystectomy unless there are specific cases where surgery is not permitted.…”
Section: Endoscopic Nasobiliary Drainage (Enbd) and Saline Preventivementioning
confidence: 99%